On Some New Seminormed Sequence Spaces Defined by a Sequence of Orlicz Functions - Bektas, Cigdem A.; Atici, Gulcan (Verlag Z Naturforsch, 2010)
In this paper, we define the new generalized difference sequence spaces c(0)(Delta(m)(v),M, u, p, q), c(Delta(m)(v), M, u, p, q), and l(infinity)(Delta(m)(v), M, u, p, q). We also study some inclusion relations between these spaces.
Keywords: Difference Sequence Spaces; Orlicz Function; Seminorm